Case report: Anti N-methyl-D-aspartate autoimmune encephalitis following a mildly symptomatic COVID-19 infection in an adolescent male - Hainmueller, Thomas; Lewis, Lambert; Furer, Tzvi (Frontiers in Psychiatry, 2023)
Background: Antibodies against N-Methyl-D-Aspartate receptors are the most commonly identified cause of autoimmune encephalitis. While predominantly associated with malignancies, cases of anti-N-Methyl-D-Aspartate receptor autoimmune encephalitis have been described after infections with herpes-simplex virus or recently in patients with severe Covid-19 disease.A previously healthy male 17-year-old adolescent acutely developed psychosis with auditory and visual hallucinations, fluctuating mental status, and an isolated seizure five weeks after a mildly symptomatic Covid-19 infection. Symptoms continued to worsen, and catatonia and additional neurological symptoms developed during initial antipsychotic treatment. Diagnostic workup revealed antibodies against N-Methyl-D-Aspartate receptors in the cerebrospinal fluid without other major abnormalities. After establishing the diagnosis, initiation of immunomodulatory therapy stopped symptom progression and led to full recovery within 2 months.The case is remarkable in that Anti-N-Methyl-D-Aspartate receptor autoimmune encephalitis developed shortly after Covid-19 infection in an adolescent despite only having mild Covid symptoms. The diagnosis should be considered in cases of acute-onset psychotic symptoms during or after Covid-19 infection, particularly in individuals without prior psychiatric history who present with atypical psychiatric or neurological features.